Edukasi Good Agriculture Practice dan Perbanyakan Bibit dengan Stek Daun dalam Budi Daya Nanas (Ananas comosus L. Merr) di Desa Curugrendeng, Kecamatan Jalan Cagak, Kabupaten Subang - Arodi Agustenta Sinulingga; Rahmad Suhartanto (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Pertanian Bogor, 2020)
Pineapple (Ananas comosus L. Merr) is a featured fruit commodity with the fourth largest production and second export in Indonesia. Jalan Cagak District is one of the centers of pineapple production but has decreased production by 38% from 2017 to 2018. The decline in production is allegedly due to low adoption of pineapple cultivation and the use of low quality seeds. One of the efforts to increase pineapple production through education activities on Production Operational Standard with the concept of Good Agriculture Practice and making a pineapple nursery demonstration plot using leaf cuttings as a pilot project for farmers. Education is provided in the form of outreach, technical guidance and socialization. The activity was conducted for pineapple farmers in Curugrendeng Village who were participants of the activity. Pineapple nursery demonstration plots using leaf cuttings planted on 12,5 m2 of land with a population of 1.961 planted cuttings.